En híbrida mezcolanza: Exile and Cultural Anxiety in Alirio Díaz Guerra’s Lucas Guevara - Jeffrey Browitt (PORTAL: Journal of Multidisciplinary International Studies, 2005)
The novel Lucas Guevara, written by the Colombian exile, Alirio Díaz Guerra, was first published in New York in 1914. It is considered to be the earliest novel about Latin American immigration to the United States written in Spanish. This fact alone merits its study. A second edition was published in 2001 along with a critical-biographical introduction, which presents the novel as the precursor of a developing genre of Hispanic immigrant literature centred on the naïve Latin American migrant who arrives in the United States inspired by the opportunities which the metropolis supposedly affords, but who nevertheless suffers a series of misfortunes because of the inability to adapt to the new culture. On the level of overt content, the novel is a lachrymose, stereotypical and conventional denunciation of the supposed evils of an amoral US society and the libertine and materialistic values underpinning it. But on a much deeper level, a picture emerges of Díaz Guerra himself as a displaced, disenchanted intellectual exile who suffers (or has suffered) an acute cultural and class anxiety in the transition from a patrician Arcadia to the heart of capitalist, industrial modernity. Through a reading of the narrative voice, and by extension the implied author, we witness his difficult coming to terms with a highly-charged New York society (in comparison to his homeland), not only because of the sexual liberation brought on by secular modernization, but also because of the close proximity of volatile, eroticised bodies on the over-crowded Lower East Side of New York, the scene of the novel and Díaz Guerra’s point of entry into the United States. The novel also provides an occasion to contrast how Díaz Guerra deals with the condition of exile, in contrast to that most emblematic of Latin American political refugees, José Martí.